Update on the distribution of Peropteryx leucoptera Peters, 1867 (Mammalia, Chiroptera, Emballonuridae): First record for the state of Sergipe, northeastern Brazil - Mikalauskas, Jefferson S. (2014)
Universidade Federal Rural do Rio de Janeiro. Programa de Pós-Graduação em Biologia Animal. Seropédica, RJ, Brasil.